Current-Mode Universal First-Order Analog Filter Using CCCIIs - Phatsornsiri, Punnavich; Torteanchai, Usa; Wongprommoon, Natapong; Kumngern, Montree; Jongchanachavawat, Wirote; Lerkvaranyu, Somkiat (My University, 2023)
This paper presents a new current-mode first-order universal analog filter using current-controlled current conveyors (CCCIIs). The proposed circuit can realize first-order sections such as all-pass, low-pass, high-pass filters with both non-inverting and inverting transfer functions into single topology. The pole frequency of these filters can be controlled electronically. The output terminals possess high impedance level which is required for cascading of current-mode circuits. The proposed analog filter is verified using SPICE simulation. The CCCII has been simulated using the 0.18 µm CMOS technology with a supply voltage of 1.8 V. The simulation result can show that it agrees well with theory.
Keywords: analog circuit; current-controlled current conveyor; current-mode circuit; first-order filter